Measuring the use of human resources practices and employee attitudes: The Linked Personnel Panel - Patrick Kampkötter; Jens Mohrenweiser; Dirk Sliwka; Susanne Steffes; Stefanie Wolter (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2015)
This paper introduces a new data source available for HRM researchers and personnel economists, the Linked Personnel Panel (LPP). The LPP is a longitudinal and representative employer-employee data set covering establishments in Germany and designed for quantitative empirical HR research. The LPP offers a unique structure. First, the data set combines employer and employee surveys that can be matched to each other. Second, it can also be linked to a number of additional administrative data sets. Third, the LPP covers a wide range of firms and workers from different backgrounds. Finally, because of its longitudinal dimension, the LPP should facilitate the study of causal effects of HR practices. The LPP employee survey uses a number of established scales to measure job characteristics and job perceptions, personal characteristics, employee attitudes towards the organisation and employee behaviour. This paper gives an overview of both the employer and employee survey and outlines the definitions, origins and statistical properties of the scales used in the individual questionnaire. – – Dieses Paper stellt eine neue Datenquelle vor, das Linked Personnel Panel (LPP), welche für Forscher in den Bereichen Personalmanagement und Personalökonomie verfügbar ist. Das LPP ist ein repräsentativer Arbeitgeber- Arbeitnehmer- Längsschnittdatensatz, der für die quantitative HR-Forschung konzipiert wurde. Das LPP bietet eine einzigartige Struktur. Erstens kombiniert der Datensatz Arbeitgeber und -Arbeitnehmerbefragungen, welche einander zugespielt werden können. Zweitens kann er zusätzlich mit administrativen Datensätzen erweitert werden. Drittens deckt das LPP eine große Bandbreite an Betrieben und Beschäftigten mit unterschiedlichen Hintergründen ab. Schließlich macht das LPP aufgrund seines Längsschnittdesigns, die Untersuchung kausaler Effekte von HR-Praktiken möglich. Die Arbeitnehmer-Befragung des LPP nutzt etablierte Skalen, um Job-Charakteristika und -Empfindungen, persönliche Charakteristika, Einstellungen der Beschäftigten gegenüber der Organisation und das Verhalten von Beschäftigten zu messen. Dieses Papier gibt einen Überblick über die Arbeitgeber- und Arbeitnehmerbefragung des LPP und stellt Definitionen, die Herkunft und die statistischen Eigenschaften der genutzten Skalen im Beschäftigtenfragebogen vor.
Keywords: J24; J81; M12; M51; M52; M53; M54; M55; 330; HR practices; matched employer-employee data; Linked Personnel Panel; employee attitudes